Analisis Penerapan OSS Berbasis Risiko dalam Mewujudkan Kepastian Hukum bagi Investor di Indonesia - Chika Fatika Sari; Sang Ayu Putu Rahayu (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study analyzes the implementation of risk-based Online Single Submission (OSS) in realizing legal certainty for investors in Indonesia. The risk-based OSS system is a licensing innovation based on Law Number 11 of 2020 concerning Job Creation and Government Regulation Number 5 of 2021, which changes the licensing paradigm from a permit-based approach to a risk-based approach. Through a normative legal approach, although designed to increase transparency, efficiency, and legal certainty, the implementation of OSS still faces challenges such as data asynchronous between the central and regional governments, institutional resistance, conflicts of authority, and gaps in regional capacity. To optimize this system, regulatory harmonization, strengthening institutional coordination, improving digital infrastructure, and mentoring for business actors, especially MSMEs, are needed. This study concludes that although not yet perfect, risk-based OSS has the potential to be a catalyst for improving the investment climate and increasing national economic competitiveness through simplifying licensing that still pays attention to aspects of security, health, and environmental protection.